The Principles of Art Therapy in Virtual Reality - Hacmun, Irit; Regev, Dafna; Salomon, Roy (Frontiers in Psychology, 2018)
In recent years, the field of virtual reality (VR) has shown tremendous advancements and is utilized in fields ranging from entertainment, scientific research, social networks, artistic creation as well as numerous approaches to employ VR for psychotherapy. While the use of VR in psychotherapy has been widely discussed, little attention has been given to the potential of this new medium for art therapy. Artistic expression in virtual reality is a novel medium which offers unique possibilities, extending beyond classical expressive art mediums. Creation in virtual reality includes options such as three-dimensional painting, an immersive creative experience, dynamic scaling and embodied expression. In this perspective paper, we present the potentials and challenges of virtual reality for art therapy and outline basic principles for its implementation. We focus on the novel qualities offered by this creative medium (the virtual environment, virtual materials and unreal characteristics) and on the core aspects of virtual reality (such as presence, Immersivity, point of view and perspective) for the practice of art therapy.